Comparison of five patellar height measurement methods in a Turkish adult cohort (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the correlation between the methods traditionally used for patellar height measurements [Insall-Salvati (IS), Modified Insall-Salvati (MIS), Blackburne-Peel (BP), Caton-Deschamps (CD)] and the plateau-patellar angle (PPA) in Turkish adult population.Material and Methods: A cross-sectional retrospective study was conducted. A total of 100 lateral knee radiographs in 30° flexion were analyzed by two blinded orthopedist independently to each other’s measurements. The average IS ratio, MIS ratio, BP ratio, CD ratio and PPA measurement were calculated by taking the average of the measurement values of both observers. The inter-observer reliability for two observers was determined using intraclass correlation coefficients (ICC). Spearman rank correlation analysis was performed to analyze correlations between mean ratios/angle measurements. Results: The mean age at the time of the radiographs was 30.18 ± 5.78 (range:20-40) years, 60% were female, and 58 radiographs were of the right knee. The mean and standard deviations of the patella height measurements were found 1.05 ± 0.12 according to the IS ratio; 1.66 ± 0.29 according to the MIS ratio; 0.91 ± 0.15 according to the CD ratio; 0.84 ± 0.14 according to the BP ratio; 24.74° ± 2.87° according to PPA measurement. There was highest inter-observer agreement between the two observers with an ICC of 0.926 (95% confidence interval: 0.89-0.950), excellent reliability, for the PPA measurement. Inter-observer agreement between two observers was good reliability for other measurements (IS, MIS, CD, BP). The highest correlation was between CD ratio and BP ratio, strong correlation, with a Pearson's correlation coefficient of 0.790.Conclusion: The PPA appears to be a feasible tool that can assess patellar height with higher reliability compared to the four most commonly used methods, in a Turkish adult population.
Keywords: Measurements; patellar height; radiographs; ratio; reliability